Dynamic factor models with common (drifting) stochastic trends - Sylvia Kaufmann; Rodney W. Strachan (Swiss National Bank, Study Center Gerzensee, 2024)
It is common to transform data to stationarity, such as by differencing and demeaning, before estimating factor models in macroeconomics. Imposing these transformations, however, limit opportunities to learn about trending behaviour. Trends and deterministic processes can play a central role in the behaviour of macroeconomic processes and so it is important to be able to characterise these features of the data. In this paper, we develop a model of common and idiosyncratic deterministic and stochastic processes in a factor model. We work with the unidentified model. A judicious choice of parameter expansion and post-processing ensures the model avoids a non-invariant specification such that the inference is data driven and the computation is efficient.
Keywords: 330; Faktorenanalyse; Dynamische Wirtschaftstheorie; Stochastischer Prozess; Bayes-Statistik; Zeitreihenanalyse; Schätztheorie; Beschäftigungsstruktur; Schätzung; USA